Modification of the Physicochemical Properties of Active Pharmaceutical Ingredients via Lyophilization - Amir Taldaev; Denis I. Pankov; Roman P. Terekhov; Anastasia K. Zhevlakova; Irina A. Selivanova (MDPI AG, 2023)
Bioavailability is an important biopharmaceutical characteristic of active pharmaceutical ingredients (APIs) that is often correlated with their solubility in water. One of the methods of increasing solubility is freeze drying (lyophilization). The article provides a systematic review of studies published from 2012 to 2022 aimed at optimizing the properties of active pharmaceutical ingredients by freeze drying. This review was carried out in accordance with the recommendations of Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). In general, 141 modifications of 36 APIs attributed to 12 pharmacological groups were reported in selected publications. To characterize the products of phase modification after lyophilization, a complex of analytical methods was used, including microscopic, thermal, X-ray, and spectral approaches. Solubility and pharmacokinetic parameters were assessed. There is a tendency to increase solubility due to the amorphization of APIs during lyophilization. Thus, the alcohol lyophilizate of dihydroquercetin is "soluble" in water compared to the initial substance belonging to the category "very poorly soluble". Based on the analysis of the literature, it can be argued that lyophilization is a promising method for optimizing the properties of APIs.